Stakeholder engagement for inclusive climate impact attribution studies - Albert Nkwasa; Inga Menke; Lisa Murken; Liliana Zaharia; Gabriela Ioana-Toroimac; Laura Müller; Melania Michetti; Muhammad Asaduzzaman; Gabriela-Adina Morosanu-Mitoșeriu; Maria Theresa Nakkazi; Vytautas Akstinas; Afnan Agramont Akiyama; et al. (Environmental Research: Climate)
Since its emergence in the 1990s, the science of attributing observed phenomena to human-induced and natural climate drivers has made remarkable progress. To ensure the relevance and uptake of climate impact attribution studies, scientists must effectively engage with stakeholders. This engagement allows stakeholders to pose key questions, which scientists can then substantiate with evidence evaluating the existence of causal links. Although significant advancements have been made in climate impact attribution science, much work remains to understand the varied requirements of different stakeholders for impact attribution findings. This perspective explores the usefulness of stakeholder engagement in climate impact attribution, the challenges it presents, and how it can be made more relevant for addressing societal questions. It advocates for prioritizing stakeholder involvement to achieve greater transparency, legitimacy, and practical application of findings. Such involvement can enhance the societal impact of attribution studies and support informed decision-making in the face of climate change.